(untitled) (Research, Society and Development, 2021)
Difficulties are often associated with suffering, but they can also be a motto for reflection and care. In this article we worked on some developments of the research developed over six years in a university hospital in the north of the country, more specifically those that emerged from clinical interventions in the service that welcomes children with autism, severe neurological syndromes, learning problems, hyperactivity, among other diagnoses. As analysts at the hospital, guided by the clinical method, we start from the freudo-lacanian assumptions that support the diagnostic suspension, until it has apprehended, in addition to organic causes, the symbolic plots imbricated with the child’s symptom. As a working tool, we use listening from parents and children, transference and the therapeutic relationship as central axes for treatment, as we believe that a hasty diagnosis can precipitate drug prescriptions that can have harmful side effects for child development. We problematize the difficulties in clinical work in institutions which, many times, work against the bet on psychic health with its particularities. It was possible to verify that there is a possibility to sensitize the team to the importance of welcoming what is of the experience, giving some possibility of binding to the subject of the unconscious. Therefore, we must effectively support the possibility of the subject’s emergence with the team, who is divided and who carries knowledge that he does not know. Important bet, both in the treatment of the child and his parents, as well as in the multidisciplinary work, in which we continue in the (im) possible exercise of intertextuality.